2002
DOI: 10.1253/circj.66.425
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus on the Tricuspid Valve in a Patient With Primary Antiphospholipid Syndrome After Implantation of an Inferior Vena Cave Filter.

Abstract: ntiphospholipid syndrome (APS) is a combination of the clinical symptoms of arterial and venous thromboembolism and the presence of autoantibodies such as anticardiolipin 2 GPI antibody, the lupus anticoagulant and the antibodies responsible for the falsepositive serologic test result for syphilis. Primary APS (PAPS) is defined by the presence of these antibodies and thromboembolic phenomena without systemic lupus erythematosus (SLE) and other disease processes. Intracardiac thrombi have been reported, 1-7 but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…12 On the other hand, insertion of IVC filters was not associated with a significant reduction in the 1-year incidence of rehospitalization for APTE. 13 A lobulated thrombus on the tricuspid valve of a patient with antiphospholipid antibody syndrome after implantation of IVC filter has been reported, 14 so the long-term effectiveness of IVC filters is controversial. Therefore, we deliberated whether to implant IVC filters, especially in the YG patients, and only the recurrent case and the patient with massive thrombosis in the IVC were implanted with a permanent IVC filter, concomitant with warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…12 On the other hand, insertion of IVC filters was not associated with a significant reduction in the 1-year incidence of rehospitalization for APTE. 13 A lobulated thrombus on the tricuspid valve of a patient with antiphospholipid antibody syndrome after implantation of IVC filter has been reported, 14 so the long-term effectiveness of IVC filters is controversial. Therefore, we deliberated whether to implant IVC filters, especially in the YG patients, and only the recurrent case and the patient with massive thrombosis in the IVC were implanted with a permanent IVC filter, concomitant with warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the aetiology, thrombosis of the tricuspid valve can be classified in four groups: caused by alterations of coagulation 6,7 (V Laiden factor, antiphospholipid antibody syndrome, etc.) incidental to deep venous thrombosis, 8–10 due to cardiac structural anomalies, 9 idiopathic forms in a structurally normal heart 11,12 and in the absence of a coagulation disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, main risk of the patients consists in unpredictable pulmonary embolization[13]. Ebato et al[14], reported that the patients have presented with symptoms of cerebral embolism and pulmonary embolism. The traditional therapy for intracardiac thrombus in pediatric patients has been surgical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%